Restoring chronology in investigative journalism - Stepovyi, Oleh (Global Prosperity, 2026)
Abstract. The article is devoted to the analysis of the processes of reconstruction of chronologies in modern investigative journalism, which operates in the conditions of a digital environment, information overload and fragmented sources. The focus is on the transformation of journalistic approaches to establishing the temporal sequence of events from the moment of the first tip to the publication of a verified investigation. The purpose of the study is to find out how modern digital tools, algorithms and analytical methods affect the construction of a reliable chronology of events in journalism. In the course of the scientific study, general scientific methods of cognition were used: analysis, synthesis, comparison, interpretation, systematization, generalization, content analysis of professional and scientific sources. The results of the study show that the investigation process has a clear temporal logic, which includes the stages of idea formation, feasibility assessment, information collection, its verification, systematization and final generalization. It is emphasized that the construction of a chronology is not only a technical task, but a key analytical element that ensures the evidentiary integrity of the material. The use of information processing technologies: databases, online registries, visualization tools, artificial intelligence tools can significantly increase the efficiency of a journalist’s work. Such studies become scientifically sound and based on real facts. In the future, journalistic investigations will be closely linked to multifactorial analysis, teamwork and the use of new ways of presenting information. The results of the study allow us to formulate a holistic vision of the approaches, tools and means that form the basis of solid journalistic material.